Pathways through trusteeship: Responding to the trustee recruitment crisis. Issue 2 (11th September 2019) - Daly, Siobhan; Slack, Richard; Brandon, Toby; Biddle, Paul
Abstract : Getting on Board 2017 suggests that the recruitment of trustees to the Board of Trustees (henceforth volunteer trustees) by charities in the United Kingdom is in a state of crisis. This report and a range of other stakeholders offer advice and guidance about recruitment, but attention to what motivates individuals to become trustees is lacking. Drawing upon the Pathways Through Participation framework, we argue that an important part of addressing the crisis in trustee recruitment is to consider the motivations of volunteer trustees in tandem with their resources and triggers for volunteering. We draw upon a study of 14 volunteer trustees of learning disability charities to explore how a critical understanding of volunteer trusteeship as a pathway through participation provides a full and rounded picture of trustee recruitment. Building on other research on volunteer recruitment and markets, we argue that recruitment can be improved when charities better understand what motivates their volunteer trustees. We recommend that charities consider trusteeship as a pathway through participation as part of their recruitment practices.